2020
DOI: 10.1186/s12879-020-05160-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards accurate exclusion of neonatal bacterial meningitis: a feasibility study of a novel 16S rDNA PCR assay

Abstract: Background: PCRctic is an innovative assay based on 16S rDNA PCR technology that has been designed to detect a single intact bacterium in a specimen of cerebro-spinal fluid (CSF). The assay's potential for accurate, fast and inexpensive discrimination of bacteria-free CSF makes it an ideal adjunct for confident exclusion of bacterial meningitis in newborn babies where the negative predictive value of bacterial culture is poor. This study aimed to stress-test and optimize PCRctic in the "field conditions" to at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Conventional 16S rRNA gene PCR/Sanger sequencing assays have the same advantage as MYcrobiota of being a broad range strategy that removes the need for an a priori knowledge of the potential bacterial pathogen before a test is performed. However, in contrast to MYcrobiota, these methods rely on relatively high concentrations of bacteria in samples and are therefore unlikely to have adequate sensitivity for exclusion of meningitis [ 14 , 15 ]. Another alternative for diagnosing meningitis is the use of commercial meningitis multiplex PCR panels, which also have the advantage of having short processing times [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional 16S rRNA gene PCR/Sanger sequencing assays have the same advantage as MYcrobiota of being a broad range strategy that removes the need for an a priori knowledge of the potential bacterial pathogen before a test is performed. However, in contrast to MYcrobiota, these methods rely on relatively high concentrations of bacteria in samples and are therefore unlikely to have adequate sensitivity for exclusion of meningitis [ 14 , 15 ]. Another alternative for diagnosing meningitis is the use of commercial meningitis multiplex PCR panels, which also have the advantage of having short processing times [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, establishing a definite diagnosis of a CNS infection by clinical chemical or cytological routine parameters is still not possible at present. Diagnosis of infections relies on the identification of the causative pathogen by culture or molecular methods (e.g., 16 s rRNA amplification [ 114 ]; multiplex polymerase chain reaction [ 115 ]; metagenomic next-generation sequencing: [ 116 ]). Recent advances in molecular methods will open new avenues for the definite diagnosis of a variety of CNS infections, particularly in the presence of atypical or mild alterations of the composition of the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies has particularly shown that targeted PCR is a useful adjunct to diagnostic and treatment modalities, providing important supplemental information compared to what is provided solely by standard bacterial culture results [ 18 ]. Attempts to determine the use of this molecular tool in the diagnosis of meningitis has also been made, although the clinical relevance remains ambiguous due to very small sample sizes in these studies [ 19 , 29 ]. In the same way, other researchers have looked into its clinical importance in blood and urine samples in the diagnosis of neonatal sepsis [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a paucity of data on the clinical utility of 16S rRNA sequencing in pediatric infections [ 2 , 6 ]. Few studies highlight the diagnostic utility of 16S rRNA sequencing in select pediatric infections [ 16 , 17 , 18 , 19 , 20 ]. Most of these studies have attempted to isolate its clinical usefulness in the diagnosis of neonatal sepsis [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%